Impact analysis and orbit reboost of payload tossing using spinning electrodynamic tether system. (10th November 2020) - Lu, Hongshi; Zabolotnov, Yuriy; Li, Aijun
Spinning electrodynamic tether systems are good platforms for payload transportation, but require orbit reboosts after one or several tossing manoeuvres. In this paper an impact analysis is proposed to predict the change of system orbits after payload tossing. Changes of key parameters (eccentricity, semi-major axis and tether spinning rate) are derived. Based on previous analysis, three control schemes are proposed to regulate current to reboost system orbits back to its original ones. One mission is assumed in numerical parts to validate the effectiveness of the proposed impact analysis and control schemes.